PREDICTIVE VALUE OF LEUKOCYTOSIS FOR DIAGNOSING ACUTE APPENDICITIS - Saleem, Muhammad Mudasir; Pervaiz, Mishal; Chaudhary, Iftikhar Ahmed (Pakistan Armed Forces Medical Journal, 2017)
Objective: To determine the predictive value of leukocytosis in the diagnosis of acute appendicitis using histopathology as gold standard.Study Design: Cross-sectional validation study.Place and Duration of Study: Department of general surgery Combined Military Hospital Bahawalpur, from Jan 2015 to Dec 2015.Material and Methods: A total of 180 patients were included in this study. Leukocyte count was done in each patient on presentation in emergency department. Following open appendectomy, resected specimens were sent for histopathological examination. Sensitivity analysis was done using two by two tables.Results: Out of 180 patients, 132 (73.3%) were male while remaining 48 (26.7%) were female with mean age of 27.2 ± 8.5 years. Sensitivity of leukocyte count in diagnosing acute appendicitis was 93.5%, specificity 64.3%, positive predictive value 89.6%, negative predictive value 75.1% and diagnostic accuracy was 86.7%.Conclusion: Raised leukocyte count was found to have high sensitivity but low specificity for diagnosing acute appendicitis. It is a poor sole inflammatory diagnostic marker for acute appendicitis necessitating additional investigations in certain cases.